2017
DOI: 10.3390/ijms18040729
|View full text |Cite
|
Sign up to set email alerts
|

Wedelolactone Acts as Proteasome Inhibitor in Breast Cancer Cells

Abstract: Wedelolactone is a multi-target natural plant coumestan exhibiting cytotoxicity towards cancer cells. Although several molecular targets of wedelolactone have been recognized, the molecular mechanism of its cytotoxicity has not yet been elucidated. In this study, we show that wedelolactone acts as an inhibitor of chymotrypsin-like, trypsin-like, and caspase-like activities of proteasome in breast cancer cells. The proteasome inhibitory effect of wedelolactone was documented by (i) reduced cleavage of fluorogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Wedelolactone, a small molecular compound isolated from Ecliptaalba and Wedelia calendulacea has attracted much attention because of its extensive pharmacological activi-ties, including hepatoprotective, anti-oxidation, anti-inflammatory, immunomodulatory and anti-fibrotic effects, etc. [87,[110][111][112] Recent researches has shown that Wedelolactone exhibited a potent anticancer activity against different solid tumors, such as breast, colon and prostate cancers, through inhibiting multiple kinases, the androgen receptor, 5-lipoxygenase and the c-Myc protein [87]. Lately, Luo et al identified Wedelolactone as a G6PD inhibitor by the high-throughput screening assay.…”
Section: Wedelolactonementioning
confidence: 99%
“…Wedelolactone, a small molecular compound isolated from Ecliptaalba and Wedelia calendulacea has attracted much attention because of its extensive pharmacological activi-ties, including hepatoprotective, anti-oxidation, anti-inflammatory, immunomodulatory and anti-fibrotic effects, etc. [87,[110][111][112] Recent researches has shown that Wedelolactone exhibited a potent anticancer activity against different solid tumors, such as breast, colon and prostate cancers, through inhibiting multiple kinases, the androgen receptor, 5-lipoxygenase and the c-Myc protein [87]. Lately, Luo et al identified Wedelolactone as a G6PD inhibitor by the high-throughput screening assay.…”
Section: Wedelolactonementioning
confidence: 99%
“…One such ethnomedicinal herb Eclipta prostrata (EP) also known as Bhringaraj in Ayurveda, is established for its anti‐inflammatory and anticancer properties 19–24 . Wedelolactone (WDL), the major coumestan derivative of this herb, is exclusively reported for anticancer effects and has been investigated to hinder the overexpression of NLRP3 inflammasome 25–34 …”
Section: Introductionmentioning
confidence: 99%
“…WDL is considered a traditional Chinese herbal medicine with strong anti-in ammatory properties [24][25][26][27][28]. Recent studies have shown that WDL can help promote hair growth [29] and is hepatoprotective [30,31], neuroprotective [32] and anti-carcinogenic [33,34].…”
Section: Introductionmentioning
confidence: 99%